2012
DOI: 10.1007/s11746-012-2102-2
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Biobased Epoxy Resins from Epoxidized Soybean Oil (ESBO) Cured with Maleic Anhydride (MA)

Abstract: Epoxidized soybean oil (ESBO), obtained from a renewable resource was used in the production of thermoset resins. Samples of the ESBO were initially treated with maleic anhydride, equal mixture of catalyst (1,3‐butanediol anhydrous and benzyldimethylamine) and the mixture was cured for 5 h at different temperatures. After the curing process, the ratio between the ESBO and the anhydride (ratio EEW:AEW) was evaluated in terms of the different mechanical properties produced using flexural, Shore D hardness and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 26 publications
4
52
0
1
Order By: Relevance
“…Previous work with ESBO derived epoxy resins has shown that T g 's are lowered with decreasing levels of anhydride ([E:A ratio) [26,42] and this was observed for all six oil/anhydride combinations in this study. This is attributed to a lowering of crosslink density within each series as the anhydride levels are decreased, (due to unreacted epoxides), and provides the polymer with an increase in elasticity from the linear chains.…”
Section: Thermal Propertiessupporting
confidence: 78%
See 4 more Smart Citations
“…Previous work with ESBO derived epoxy resins has shown that T g 's are lowered with decreasing levels of anhydride ([E:A ratio) [26,42] and this was observed for all six oil/anhydride combinations in this study. This is attributed to a lowering of crosslink density within each series as the anhydride levels are decreased, (due to unreacted epoxides), and provides the polymer with an increase in elasticity from the linear chains.…”
Section: Thermal Propertiessupporting
confidence: 78%
“…This correlates to the greater proportion of epoxidized linoleic chains and is in agreement with the trends found by Webster [37] for the polymerization of epoxy sucrose esters and cyclic anhydrides. The cure temperature range was similar to that observed for epoxy resins derived from ESBO and maleic anhydride (C T = 150°C) [26]. It was also possible to determine the enthalpy of polymerization from the area under the DSC curve.…”
Section: Curing Kineticssupporting
confidence: 56%
See 3 more Smart Citations